Do Doppler Studies Enhance Surveillance of Uncomplicated Monochorionic Diamniotic Twins?. (1st April 2015) - Pessel, Cara; Merriam, Audrey; Vani, Kavita; Brubaker, Sara G.; Zork, Noelia; Zhang, Yuan; Simpson, Lynn L.; Gyamfi-Bannerman, Cynthia; Miller, Russell
Abstract : Objectives: To determine whether isolated abnormal Doppler indices before 28 weeks predict adverse pregnancy outcomes in uncomplicated monochorionic diamniotic (MCDA) twins. Methods: A retrospective cohort study of MCDA twin pregnancies receiving antenatal testing at a single center between 2007 and 2013 was conducted. Sonographic surveillance, including Doppler velocimetric studies of the umbilical artery, ductus venosus, and middle cerebral artery of each twin, was initiated by 28 weeks and repeated at least every 2 weeks. All pregnancies were deemed "uncomplicated" at initial sonography, without evidence of polyhydramnios, oligohydramnios, intrauterine growth restriction, twin growth discordance of at least 20%, structural or chromosomal anomalies, or unclear chorionicity. Pregnancies were divided into 2 groups: those with isolated Doppler abnormalities before 28 weeks and those with normal Doppler indices. The primary outcome was a composite including twin‐twin transfusion syndrome, intrauterine growth restriction of more than 1 twin, growth discordance of at least 20%, preterm delivery before 34 weeks for fetal indications, or demise of more than 1 fetus. Results: Ninety‐six patients were included, with 22 (22.9%) having isolated Doppler abnormalities before 28 weeks. The incidence of the primary outcome did not differ between groups (36.4% versus 28.4%; P = .47). The abnormal Doppler group underwent a greater number of sonographic examinations (15 versus 10; P = .001) and more antenatal admissions for fetal concerns (50.0% versus 12.2%; P < .001). Conclusions: Isolated Doppler abnormalities are commonly encountered in uncomplicated MCDA pregnancies before 28 weeks yet are not clearly predictive of twin‐specific complications. Doppler abnormalities were associated with increased sonographic surveillance and antenatal hospitalizations, suggesting an influence on physician practice patterns. Data may not support Doppler studies before 28 weeks for routine MCDA twin monitoring.